2021
DOI: 10.1007/s11897-021-00515-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Myocardial Deformation Applying CMR-Feature-Tracking—All About the Left Ventricle?

Abstract: Purpose of Review Cardiac magnetic resonance-feature-tracking (CMR-FT)-based deformation analyses are key tools of cardiovascular imaging and applications in heart failure (HF) diagnostics are expanding. In this review, we outline the current range of application with diagnostic and prognostic implications and provide perspectives on future trends of this technique. Recent Findings By applying CMR-FT in different cardiovascular diseases, increasing evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 137 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…These measurements provide objective evaluations of subclinical RV dysfunction before clinically obvious RVEF reductions. The CMR-FT method has recently been identified as a novel method of assessing the quantitative function of the biventricular myocardium [12,21]. This technology is based on tissue voxel motion-tracking technology derived from CMR cine imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements provide objective evaluations of subclinical RV dysfunction before clinically obvious RVEF reductions. The CMR-FT method has recently been identified as a novel method of assessing the quantitative function of the biventricular myocardium [12,21]. This technology is based on tissue voxel motion-tracking technology derived from CMR cine imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with type 2 diabetes have been subjected to echocardiographic studies to determine how much strain they are under. With cardiac magnetic resonance feature tracking (CMR-FT), a novel method has been developed for quantifying left and right ventricular myocardial deformation using high-resolution images [10][11][12]. Further, studies have shown that speckle-tracking echocardiography (STE) is a reliable, reproducible, and accurate method of measuring LV deformations in a wide range of clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nayyar, D [ 27 ] et al described a compensatory increase in atrial booster pump function in the presence of impaired conduit function after STEMI. LA strain reflects atrial compliance and atrial contractility and relaxation, modulated by the descent of the LV base during systole [ 28 , 29 ]. Therefore, as an early parameter, LA strain may be more helpful in detecting diastolic alterations before LA enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…When the LV base descends during systole, the LA strain re ects atrial compliance and, to a lesser extent, atrial contractility and relaxation. [44,45] . It is clear that LA strain has a more clinical application.…”
Section: Discussionmentioning
confidence: 99%